2010
DOI: 10.2147/ibpc.s9691
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of amlodipine and olmesartan medoxomil fixed-dose combination in achieving blood pressure goals

Abstract: Hypertension remains a significant health burden in the United States, with almost one in three adults affected, and is an independent risk factor for cardiovascular and renal disease. The goal of antihypertensive treatment is to reduce cardiovascular and renal morbidity and mortality by reducing blood pressure (BP). Guidelines recommend a target BP of <140/90 mmHg, with a more stringent goal of <130/80 mmHg for patients with diabetes and chronic renal disease. However, BP goal attainment rates remain low and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(106 reference statements)
1
1
0
Order By: Relevance
“…Other studies have reported that fixed-dose combinations offer advantages of convenience. 7,18 The literature correlates well with the findings in this research and it appears to be generally accepted that the use of a combination pill will improve the convenience of taking regular medication, leading to greater adherence to regimens and improved health outcomes.…”
Section: Participants Valued Their Medicalsupporting
confidence: 78%
“…Other studies have reported that fixed-dose combinations offer advantages of convenience. 7,18 The literature correlates well with the findings in this research and it appears to be generally accepted that the use of a combination pill will improve the convenience of taking regular medication, leading to greater adherence to regimens and improved health outcomes.…”
Section: Participants Valued Their Medicalsupporting
confidence: 78%
“…2 Review of other CCB/ARB FDCs in mild-to-severe hypertension, including amlodipine/olmesartan and amlodipine/telmisartan, supports the simplified fixed-dose approach in long-term therapy, with benefits for safety, efficacy and compliance relative to monotherapies. 20,21 We are aware of no long-term clinical studies in hypertension that directly compare the efficacy and safety of different CCB/ARB FDCs.…”
Section: Parametermentioning
confidence: 99%